2018
DOI: 10.1074/jbc.ra118.002007
|View full text |Cite
|
Sign up to set email alerts
|

Staphylopine, pseudopaline, and yersinopine dehydrogenases: A structural and kinetic analysis of a new functional class of opine dehydrogenase

Abstract: Opine dehydrogenases (ODHs) from the bacterial pathogens ,, and perform the final enzymatic step in the biosynthesis of a new class of opine metallophores, which includes staphylopine, pseudopaline, and yersinopine, respectively. Growing evidence indicates an important role for this pathway in metal acquisition and virulence, including in lung and burn-wound infections () and in blood and heart infections (). Here, we present kinetic and structural characterizations of these three opine dehydrogenases. A stead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
65
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(69 citation statements)
references
References 42 publications
(50 reference statements)
4
65
0
Order By: Relevance
“…The structure of CntM have been solved in a binary/tertiary complex with NADPH or NADPH and xNA, revealing the residues that are involved in the complex formation and building the active site [8,32]. First focusing on the NADPH binding site of SaCntM (Figure 2A) we observed that the phosphate group of NADPH is sandwiched by the side chains of two positively charged residues (R33 and K39) that are rather conserved in the CntM family.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The structure of CntM have been solved in a binary/tertiary complex with NADPH or NADPH and xNA, revealing the residues that are involved in the complex formation and building the active site [8,32]. First focusing on the NADPH binding site of SaCntM (Figure 2A) we observed that the phosphate group of NADPH is sandwiched by the side chains of two positively charged residues (R33 and K39) that are rather conserved in the CntM family.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, nicotianamine-like metallophores have been identified in some bacteria as playing an important role in metal acquisition strategies. Staphylopine, pseudopaline and yersinopine are the three examples currently known and recently identified in S. aureus [5], P. aeruginosa [6,7] and Y. pestis [8] respectively. The biosynthesis of these nicotianamine-like metallophores occurs in two or three steps depending on the species.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations